-5g=-6g+10

Simple and best practice solution for -5g=-6g+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5g=-6g+10 equation:



-5g=-6g+10
We move all terms to the left:
-5g-(-6g+10)=0
We get rid of parentheses
-5g+6g-10=0
We add all the numbers together, and all the variables
g-10=0
We move all terms containing g to the left, all other terms to the right
g=10

See similar equations:

| 9+8u+7=10u-4 | | 5x+21=36 | | 10+5u=4u | | 50+3t=t+82= | | 6x-2=-2x-10 | | 9x+21=6x+12 | | -8z=-6-10z | | 2m+17=3m+5= | | 15-3x-1x=5 | | 18+w=3w+6= | | 7u=5=2u-10 | | 7-n=-2-2n | | 2(3-x)=5(4x-1 | | x=34=13 | | 4t+7=2t+20= | | -6w+8=-7w | | 5a-a-6a-15+7a=12-a-2a+12-3a | | 4x+3-6x=155 | | 247=194-v | | -6x-16=-3x-25 | | 10-b=9b | | x+5+9x-5=10 | | 162=81-x | | 3n—5=10 | | 2-3x-7x=15 | | X+12+2x+6=30 | | -10-u=4u | | 27w+7=4w^2+4w+1 | | 8-6z=-7z | | 13+x+8=3x-1 | | 3(2x-1)+3=x+15 | | 8x+5x-1=12 |

Equations solver categories